Serum High Sensitivity C-Reactive Protein and Uric Acid as Biomarkers of Left Ventricular Hypertrophy in Hypertensive Patients in Makurdi, Nigeria (African Journal of Biomedical Research, 2023)
Hypertension is a major cause of mortality worldwide and a major global health challenge. Hypertensive heart diseases including left ventricular hypertrophy are chronic complications of hypertension and are associated with worsening prognosis and progression to poor outcomes in affected patients. It is imperative that left ventricular hypertrophy is detected early to forestall these untoward outcomes. Current diagnostic tools available often detect structural and functional defects, however markers like hsCRP and uric acid are expressed much earlier before structural defects begin and may help to delay and possibly prevent hypertensive heart diseases when detected early. A total of 211 hypertensive patients with and those without left ventricular hypertrophy were recruited, hsCRP and uric acid were measured and compared between the two groups. Both markers were significantly elevated in hypertensive patients with left ventricular hypertrophy compared to those without left ventricular hypertrophy. hsCRP and uric acid also showed high sensitivity (76.1% vs 77.9%) and diagnostic efficiency (70.1% vs 71.1%) when used individually and when both are combined (77.6% and 74.4%), in detecting left ventricular hypertrophy in hypertensive patients. Thus, these markers may be employed in monitoring hypertensive patients to improve their quality of life and treatment outcomes